Kinds of figurative language in three songs of Disney movies original soundtrack - Wati Purnama Sari (LADU: Journal of Languages and Education, 2021)
Background: Figurative language are quite popular in song’s lyric because we can hide our messages or what we had experienced or felt. That became a reason why we should learn more about kinds of figurative language in order to understand more about the real meanings that are conveyed in the songs. Purpose: The aim for this research is to discover the kinds of figurative language in three songs of Disney Movies Original Soundtrack. Design and methods: In this research, the researcher used qualitative methods. In analyzing the data, the researcher used Mezo’s theory of figurative language. The source of data for this research are from Disney movies original soundtrack namely, the song entitled “Lead the way” from Raya and the last dragon movie, “Love, brave and true” from Mulan movie and “How does a moment last forever” from the Beauty and the Beast movie. The data from this research are the sentences that had figurative language. Result: After doing an analysis, there are 21 data appeared. The researcher discovered 6 kinds of figurative language from those data namely, Hyperbole (6 data), Metaphor (5 data), Personification (4 data), Litotes (2 data), Simile (2 data), and Synecdoche (2 data).